Treatment of pes varus using locking plate fixation in seven Dachshund dogs - Petazzoni, M.; Nicetto, T.; Vezzoni, A.; Piras, A.; Palmer, R. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objectives: To describe the surgical treatment of pes varus in Dachshund dogs by medial opening wedge osteotomy of the distal tibia stabilized with a locking plate system and to retrospectively report the clinical and radiographic outcomes.Materials and methods: Lameness in nine limbs of seven Dachshund dogs with pes varus deformity was treated with corrective osteotomy at or near the centre of rotation of angulation as defined by the intersection of the proximal and distal mechanical axes determined on caudo-cranial radiographs. Outcomes evaluated included comparison of preand postoperative radiographic measurements of frontal angulation and lameness assessment.Results: Lameness resolved in eight limbs and improved in one limb. All osteotomies healed and no implant complications were detected. Mean preoperative radiographic measurements were: mechanical medial proximal tibial angle (mMPTA) = 91.1° (range 87.6°-95°), mechanical medial distal tibial angle (mMDTA) = 62.1° (range 51.9°-69.6°). Mean postoperative measurements were: mMPTA 92.4° (range 78°-97.5°), mMDTA 81.8° (range 76°-87°). Measurable undercorrection was common, though seldom visually or functionally evident.Clinical significance: Pes varus deformity in Dachshunds can be treated by medial opening wedge osteotomy of the distal tibia stabilized with a locking plate system. Care to preserve the lateral cortex of the osteotomy may help avoid under-correction.
Keywords: Pes varus; Dachshund; open wedge; osteotomy; locking plate fixation; Fixin plates